Organ preservation following radiation therapy and concurrent intra‐arterial low dose cisplatin infusion for advanced T2 and T3 laryngeal cancer: Long‐term clinical results from a pilot study. Issue 1 (8th January 2020) - Ono, Takeharu; Tanaka, Norimitsu; Tanoue, Syuichi; Miyata, Yusaku; Muraki, Koichiro; Tsuji, Chiyoko; Ogo, Etsuyo; Aso, Takeichiro; Chitose, Shun‐ichi; Shin, Buichiro; Kakuma, Tatsuyuki; Etoh, Hidehiro; et al.
Abstract: Background: This pilot study evaluated the long‐term outcomes of patients with advanced T2 or T3 squamous cell carcinoma of the larynx (SCC‐L) who were treated with selective intra‐arterial cisplatin and concomitant radiotherapy (RADPLAT). Methods: We retrospectively investigated the data of 49 patients with advanced T2 or T3 SCC‐L who received a RADPLAT regimen with low‐dose cisplatin. Results: The 5‐year locoregional control, disease‐specific survival, and overall survival rates were 83.3%, 88.1%, and 82.6%, respectively, while the 5‐year freedom from laryngectomy, laryngectomy‐free survival, and laryngo‐esophageal dysfunction‐free survival rates were 89.6%, 79.4%, and 77.1%, respectively. The incidences of grade 3‐4 hematologic and nonhematologic toxicities were 18% and 6%, respectively. Although two patients (4%) developed late toxicities within 5 years following RADPLAT, no other events were noted beyond 5 years. Conclusion: This pilot study demonstrated that RADPLAT is feasible and safe and yielded favorable survival outcomes and functional laryngeal preservation in patients with advanced T2 or T3 SCC‐L. Level of evidence: 3